2022
DOI: 10.1101/2022.02.27.482144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In utero delivery of miRNA induces epigenetic alterations and corrects pulmonary pathology in congenital diaphragmatic hernia

Abstract: Structural fetal diseases, such as congenital diaphragmatic hernia (CDH) can be diagnosed prenatally. Neonates with CDH are healthy in utero as gas exchange is managed by the placenta, but impaired lung function results in critical illness from the time a baby takes its first breath. During fetal development, lungs are capable of remarkable growth and the fetus does not yet require lung function for gas exchange. MicroRNA (miR) 200b and its downstream targets in the TGF beta pathway are critically involved lun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Through in vitro studies, they found that treatment of miR200b can induce TGF‐β signaling pathways and increase the occurrence of branching morphologies. In their study, they delivered miR200b in utero using PACE NPs to treat a rat model of CDH, and they found that in utero delivery of miR200b induces alterations in the TGF‐β pathway, leads to pulmonary vascular remodeling, and improves PH 45 . Similarly, a recent experiment by Da et al on the treatment of abdominal aortic aneurysms (TAA) in mice found that the application of AGGF could inhibit vascular inflammation and remodeling of TAA by blocking the cleavage of LAP‐TGF‐β1 to form mature TGF‐β1 and inhibiting Smad2/3 and ERK1/2 phosphorylation in VSMCs 46 .…”
Section: Vascular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through in vitro studies, they found that treatment of miR200b can induce TGF‐β signaling pathways and increase the occurrence of branching morphologies. In their study, they delivered miR200b in utero using PACE NPs to treat a rat model of CDH, and they found that in utero delivery of miR200b induces alterations in the TGF‐β pathway, leads to pulmonary vascular remodeling, and improves PH 45 . Similarly, a recent experiment by Da et al on the treatment of abdominal aortic aneurysms (TAA) in mice found that the application of AGGF could inhibit vascular inflammation and remodeling of TAA by blocking the cleavage of LAP‐TGF‐β1 to form mature TGF‐β1 and inhibiting Smad2/3 and ERK1/2 phosphorylation in VSMCs 46 .…”
Section: Vascular Remodelingmentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) is a pulmonary dysplasia characterized by reduced distal airway branches, reduced alveolar numbers, and thickening of the lung wall. Ullrich et al 45 found that the expression of microRNA(miR)200b in tracheal secretions of fetuses that survived fetoscopic endoluminal tracheal occlusion treatment was higher than that of fetuses that did not respond to tracheal occlusion. The microRNA200 family inhibits several genes in the TGF‐β pathway.…”
Section: Vascular Remodelingmentioning
confidence: 99%